(3TQM Yjhf GdMceIs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3Gddge jG NGdb GdSehGJ hGdCQV CeG HYO aEf cJGH Yjhf GdMceI CNHGQg SjWQJ ai UMGFa GdeaGNQI hcJHJ Ydi LgJg Gdadc GdOGFQI bGd GdTjN GdQFjS gPG GdcJGH jTJedY Ydi KdGKI CbSGe efWb hWHjYi hEdgi s
(3BNQgG (B:s
(3Yf EeJRGL CMcGe Gdage hGdNjGd hGdeQGO efbhdg hba GdfXQ Ydi LdGd GdMb GdChd aCSFdc HhLhH QMeJc hEfbWGY MLJi hHabQi Edjc Je GdcJGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1186s
Keywords: (3GdadSaI hGdefWbs